Manipulating graded exercise test variables affects the validity of the lactate threshold and VO2peak - Jamnick, N.; Botella Ruiz, J.; Pyne, D. B.; Bishop , D, J. (PLOS ONE, 2018)
Background To determine the validity of the lactate threshold (LT) and maximal oxygen uptake () determined during graded exercise test (GXT) of different durations and using different LT calculations. Trained male cyclists (n = 17) completed five GXTs of varying stage length (1, 3, 4, 7 and 10 min) to establish the LT, and a series of 30-min constant power bouts to establish the maximal lactate steady state (MLSS). was assessed during each GXT and a subsequent verification exhaustive bout (VEB), and 14 different LTs were calculated from four of the GXTs (3, 4, 7 and 10 min)—yielding a total 56 LTs. Agreement was assessed between the highest measured during each GXT () as well as between each LT and MLSS. and LT data were analysed using mean difference (MD) and intraclass correlation (ICC). Results The value from GXT1 was 61.0 ± 5.3 mL.kg-1.min¹ and the peak power 420 ± 55 W (mean ± SD). The power at the MLSS was 264 ± 39 W. from GXT3, 4, 7, 10 underestimated by ~1-5 mL.kg-1.min¹. Many of the traditional LT methods were not valid and a newly developed Modified Dmax method derived from GXT4 provided the most valid estimate of the MLSS (MD = 1.1 W; ICC = 0.96). Conclusion The data highlight how GXT protocol design and data analysis influence the determination of both and LT. It is also apparent that and LT cannot be determined in a single GXT, even with the inclusion of a VEB.